Modeling genetic epilepsies in a dish. Issue 1 (11th July 2019) - Niu, Wei; Parent, Jack M.
Abstract: Human pluripotent stem cells (hPSCs), including embryonic and induced pluripotent stem cells, provide a powerful platform for mechanistic studies of disorders of neurodevelopment and neural networks. hPSC models of autism, epilepsy, and other neurological disorders are also advancing the path toward designing and testing precision therapies. The field is evolving rapidly with the addition of genome‐editing approaches, expanding protocols for the two‐dimensional (2D) differentiation of different neuronal subtypes, and three‐dimensional (3D) human brain organoid cultures. However, the application of these techniques to study complex neurological disorders, including the epilepsies, remains a challenge. Here, we review previous work using both 2D and 3D hPSC models of genetic epilepsies, as well as recent advances in the field. We also describe new strategies for applying these technologies to disease modeling of genetic epilepsies, and discuss current challenges and future directions. Key Findings: We review the use of human pluripotent stem cells to model genetic epilepsies, including 2‐D cultures, brain organoids and the application of gene editing technology. We also discuss current challenges and future directions for the field.